Proteasome inhibitors induce growth inhibition and apoptosis in myeloma cell lines and in human bone marrow myeloma cells irrespective of chromosome 13 deletion - Zavrski, Ivana; Naujokat, Cord; Niemöller, Kathrin; Jakob, Christian; Heider, Ulrike; Langelotz, Corinna; Fleissner, Claudia; Eucker, Jan; Possinger, Kurt; Sezer, Orhan (Journal of cancer research and clinical oncology, 2003)
PURPOSE: In this study, we investigated the effects of cell-permeable proteasome inhibitors MG-132, MG-262, PSI, and lactacystin on multiple myeloma cell lines OPM-2, U266, RPMI 8226-S, freshly isolated plasma cells with or without deletion of chromosome 13 from patients with multiple myeloma and plasma cell leukemia, and CD34+ human hematopoietic stem cells. The effects of proteasome inhibitors on cell cycle progression, cell growth, and apoptosis were determined. METHODS: MTT-assay was used to examine the cytotoxicity, and annexin-V staining to quantify apoptosis. Cell cycle analyses were performed using 7-ADD and Ki-67 staining by flow cytometry. RESULTS: PSI was the most potent proteasome inhibitor among those tested with a half maximal cytotoxicity (IC(50)) of 5.7 nM, followed by MG-262, MG-132, and lactacystin. Growth inhibition occurred irrespective of chromosome 13 status. Cell cycle arrest occurred in a dose- and time-dependent manner. Low, subapoptotic dosages led to a partial loss of Ki-67 antigen, whereas apoptotic dosages led to reduced Ki-67 levels. Apoptosis was partially dependent on activation of caspase-3, since Ac-DEVD-cho, a caspase-3 inhibitor, could reduce apoptosis significantly. The cytotoxicity of the four proteasome inhibitors tested was significantly lower in human hematopoietic stem cells than in myeloma cells. CONCLUSIONS: Our results show that proteasome inhibitors induce time- and dose-dependent cell cycle alterations, growth inhibition, and apoptosis in human myeloma cells irrespective of chromosome 13 deletion.
Gesehen am 19.02.2021